Local autonomy and interregional equality - Alexander W. Cappelen; Bertil Tungodden (University of Oslo, Department of Economics, 2004)
This paper shows how two important interregional transfer schemes,the foundation grant and the power equalization grant, can be seen as two different interpretations of equal opportunity ethics. It provides characterizations of both transfer schemes by the use of basic liberal egalitarian principles. Both the foundation grant and the power equalization grant scheme make use of specific reference levels. The paper also shows how reasonable requirements on the transfer schemes restrict the set of possible reference levels.
Keywords: E62; 330; transfer schemes; foundation grant; power equalization grant; liberal egalitarian principles; Kommunale Selbstverwaltung; Finanzausgleich; Entwicklungskonvergenz